Morphological and mechanical response characterization of nanofiber aggregates of pva produced by electrospinning sol-gel process (2013)
This work deals with the preparation of poly (vinyl alcohol) solutions composed of a surface active agent, an acid and water. With this solution firstly electrospun nanofiber mats and then nanofiber aggregates were obtained by electrospinning/sol-gel process. The samples were morphologically characterized using scanning electron microscopy (SEM) and Atomic Force Microscopy (AFM), obtaining superficial roughness values, distribution and average diameter before and after the electrospinning/sol-gel process. The PVA nanofiber aggregate reached a maximum strength and a modulus of 90 MPa and 2.55 GPa, respectively. Experimental results show that these fibers have a potential use as secondary reinforcement materials in cementitious composites.